2009
DOI: 10.1007/978-3-642-00515-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Test Data Generation of Bytecode by CLP Partial Evaluation

Abstract: Abstract. We employ existing partial evaluation (PE) techniques developed for Constraint Logic Programming (CLP) in order to automatically generate test-case generators for glass-box testing of bytecode. Our approach consists of two independent CLP PE phases. (1) First, the bytecode is transformed into an equivalent (decompiled) CLP program. This is already a well studied transformation which can be done either by using an ad-hoc decompiler or by specialising a bytecode interpreter by means of existing PE tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…But, when trityp=1, i==j holds and this incorrect version may answer that the triangle is isosceles while it may not be a triangle at all. For example, it will return 2 when (i,j,k)= (1,1,2). Table 4 depicts the experimental results.…”
Section: An Incorrect Tritype Programmentioning
confidence: 93%
“…But, when trityp=1, i==j holds and this incorrect version may answer that the triangle is isosceles while it may not be a triangle at all. For example, it will return 2 when (i,j,k)= (1,1,2). Table 4 depicts the experimental results.…”
Section: An Incorrect Tritype Programmentioning
confidence: 93%
“…In this section, we summarize the CLP-based approach to TDG for imperative languages introduced in [1] and recently extended to object-oriented languages with dynamic memory in [10]. For simplicity, we do not take aliasing of references into account and simplify the language by excluding inheritance and virtual invocations.…”
Section: Clp-based Test Case Generationmentioning
confidence: 99%
“…block-k) which limits to a threshold k the number of times we iterate on loops (resp. visit blocks in the control flow graph [1]). Among the wide variety of approaches to TDG (see [20]), our work focuses on glass-box testing, where testcases are obtained from the concrete program in contrast to black-box testing, where they are deduced from a specification of the program.…”
Section: Introductionmentioning
confidence: 99%
“…Constraint Logic Programming (CLP) was used for test generation of programs (e.g., [16,17,18,1]) and provides a nice implementation tool extending symbolic execution techniques [6]. Gotlieb et al showed how to represent imperative programs as constraint logic programs: InKa [16] was a pioneer in the use of CLP for generating test data for C programs.…”
Section: Related Workmentioning
confidence: 99%
“…Instead of translating the program and the property into a big propositional formula and using a constraint solver at the last stage of BMC, constraint solving is integrated with state exploration to prune the state space as early as possible. More precisely, our strategy is based on the following observation: when the program is in an SSA-like form 1 , a faulty path can be built in a dynamic way. The Control Flow Graph (CFG) does not have to be explored in a top down (or bottom up) way, and compatible blocks can just be collected in a non-deterministic way.…”
Section: Introductionmentioning
confidence: 99%